On the relative importance of ecology and geographic isolation as drivers for differentiation of call types of red crossbill Loxia curvirostra in the Palearctic. (26th October 2020) - Martin, Ralph; Rochefort, Julien; Mundry, Roger; Segelbacher, Gernot
Abstract : Efforts to understand the process of speciation have been central to the research of biologists since the origin of evolutionary biology as a discipline. While it is well established that geographic isolation has played a key role in many speciation events, particularly in birds, there is ongoing debate about how frequent speciation is in the partial or complete absence of geographical isolation. In the red crossbill Loxia curvirostra, good arguments do exist for sympatric speciation processes. In this species, several classes of calls are clustered in distinct groups, so‐called 'call types', which mate assortatively. Often, several call types can be found at a single site, breeding and feeding next to each other. It has been hypothesized that red crossbill call types evolved by specialising in extracting seeds from cones of different conifer species. Alternatively, call types might have evolved in temporal geographic isolation. Within Europe, little is known about the distribution of the various call types and preferences for distinct food resources. In this study, we analysed the temporal and spatial occurrence of red crossbill call types in the Palearctic, investigated potential reasons for call‐type composition at a site, and compared the occurrence of call types with the fructification of conifers. Call‐type composition changed with site and season but hardly with conifer species. With our data, we could localise range areas of twelve different call types, which cannot be explained by conifer species occurrence. Therefore, we suggest that call types evolved in parapatry in most of the northern Palearctic region, and, although contradictory results exist from Iberia, we argue that differentiation might be driven by the same drivers there as well. Additionally, we discuss the potential influence of anthropogenic changes of forest composition and distribution on call types, which offers a unique possibility for future studies.